2014
DOI: 10.5713/ajas.2013.13816
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Rescues the Poor Developmental Capacity of Aged Porcine Oocytes

Abstract: Unfertilized oocytes age inevitably after ovulation, which limits their fertilizable life span and embryonic development. Rapamycin affects mammalian target of rapamycin (mTOR) expression and cytoskeleton reorganization during oocyte meiotic maturation. The goal of this study was to examine the effects of rapamycin treatment on aged porcine oocytes and their in vitro development. Rapamycin treatment of aged oocytes for 24 h (68 h in vitro maturation [IVM]; 44 h+10 μM rapamycin/24 h, 47.52±5.68) or control oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…GDF-9 (a member of the transforming growth factor-β family: TGF-β) is an oocyte-secreted growth factor that plays essential roles in oocyte maturation, cumulus expansion, and oogenesis [47]. It has been shown that the cytoplasmic maturation can be assayed through the expression of GDF-9 and GSH levels [38,47,48]. Exposure of COCs during oocyte maturation to oocyte-secreted factors (OSFs) such as GDF-9 significantly enhanced oocyte developmental competence [49].…”
Section: Discussionmentioning
confidence: 99%
“…GDF-9 (a member of the transforming growth factor-β family: TGF-β) is an oocyte-secreted growth factor that plays essential roles in oocyte maturation, cumulus expansion, and oogenesis [47]. It has been shown that the cytoplasmic maturation can be assayed through the expression of GDF-9 and GSH levels [38,47,48]. Exposure of COCs during oocyte maturation to oocyte-secreted factors (OSFs) such as GDF-9 significantly enhanced oocyte developmental competence [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these factors are important determinants of the efficiency of embryo production in vitro. Indeed, these parameters decrease when oocytes are exposed to stresses such as aging (Lee et al, ), oxidative stress induced by H 2 O 2 or sodium fluoride (Liang et al, ; Yazaki, Hiradate, Hoshino, Tanemura & Sato, ), and heat stress induced by high temperature (Gharibzadeh et al, ). In this study, oocyte survival and PB extrusion rates were lower in the 0 AL group than in the control group, and these decreases were prevented in the 1 AL group (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Spindle microtubules span from centrosomes to centromeres and regulate the cell cycle by arranging the chromosomes (Rienzi et al, ). When a matured oocyte is not fertilized, the ultrastructures of centrosomes and microtubules are disrupted, leading to spindle abnormalities and chromosome unpacking (Lee et al, ; Saito et al, ). We found that the percentage of oocytes with normal spindles decreased upon in vitro aging, and that allicin treatment prevented this decrease (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations